Inhibition of Multiplication of Mycobacterium leprae by Polyinosinic-Polycytidylic Acid - Levy, Louis (1977)
Contrary to the results of an earlier study in which polyinosinic-polycytidylic acid [poly(I:C)] administered intraperitoneally to mice had no effect on multiplication of Mycobacterium leprae in the mouse footpad, the local administration of poly(I:C) every 12 h for 15 doses during logarithmic multiplication was found both to inhibit bacterial multiplication and to produce high tissue levels of interferon (IF). Local administration of poly(I) alone inhibited multiplication of M. leprae to almost as great a degree without at the same time producing a measurable IF titer in the footpad tissues. Mouse IF and “mock” IF both inhibited bacterial multiplication to the same degree, but administration of only the former resulted in a measurable IF titer. Polyadenylic-polyuridylic acid administered locally neither inhibited multiplication nor induced IF; fetal calf serum, administered in the same concentration as found in the preparations of IF and mock IF, was modestly inhibitory, without inducing IF. Thus, the local administration of poly(I:C) appears to have inhibited multiplication of M. leprae independently of IF induction.